Use of Medicinal Plants in the Alternative Treatment of Breast Cancer - , Quintão Amaral; , Semirames do Nascimento Silva; , Leonardo Afonso Pereira da Silva Filho; , Agdylannah Felix Vieira; , Luís Paulo Firmino Romão da Silva; , Mailson Gonçalves Gregório (Archives of Current Research International, 2023)
Breast cancer is the second most frequent type of cancer in the world and the most common among women and its incidence has been increasing over time. From the 70s of the last century, the use of alternative therapies became popular, with their adherence increasing annually, starting to be used by various groups, including cancer patients. Plants are one of the oldest forms that the population of various regions and cultures in the world uses as a palliative method and with a medicinal purpose for the treatment of various diseases, including cancer. The objective of this study was to identify the use of medicinal plants in the alternative treatment of breast cancer. The survey data were collected from February to March 2022, using a semi-structured questionnaire. The participation of women in the research stood out that of men. The age group of 31 to 40 years stood out from the others, the use of medicinal plants is common in 66.7% of the interviewees. About breast cancer, 31.5% reported that there are cases in the family, which are treated with radiotherapy, chemotherapy, surgery and allopathic medication. 85.2% who believe in treatment with the use of medicinal plants, the most cited plants were lemon balm, lemongrass and mint, chamomile, boldo and aloe, these are generally used by respondents. Aloe vera, soursop, basil and noni were cited as plants used to treat breast cancer. The leaves are the main part used by the interviewees, and the main form of use was infusion/tea, mentioned 45 times by the participants. After starting to use the plants, 85.7% stated that their symptoms had improved. As for the origin of knowledge about the use of medicinal plants, most claimed to have learned from their parents and grandparents. Medicinal herbs are mainly purchased at markets/fairs. For 61.1% of participants, medicinal plants do not pose health risks.